Analisis Status Ekonomi dan Tingkat Pendidikan Terhadap Pernikahan Usia Dini di Desa Kubah Sentang – Kec. Pantai Labu - Ardhia Prameswari; Ayu Elvina; Ayu Ismah Azizah Kurinci; Hanifah Oktaviani Fakhri; Niki Ayu Purwanti; Rizki Ramadani; Khalid Khalid (UNIVED Press, 2023)
This study aims to analyze how the economic status and education level of marriage at an early age in the village of Kubah Sentang Kec. Pantai Labu Deli Serdang. Where early marriage itself has an age limit according to WHO, which is 11-20 years, while in the village of Kubah Sentang, the number of ages for marriage is between 16 and 19 years. Early marriage usually occurs because of various factors, including the low level of education which indirectly affects the mindset in understanding an existing problem. Economic factors also have a big influence on the event of early marriage due to reasons that can reduce the burden of dependents that are responsible for parents. Researchers conducted research in the village of Kubah Sentang and the data obtained is that in this village poverty reaches 30%. In addition, the unemployment rate of the residents of the Sentanf Dome is also high, reaching 55%. In the village of Kubah Sentang also has a very low level of education, namely only stepping on to the level of Elementary School and Junior High School. Based on the data above, this also causes many early marriages to occur in the people of the village of Kubah Sentang. In this study, the researcher used a qualitative research method using a descriptive approach and the data obtained by interviewing the residents of the village of Kubah Sentang Kec. Pantai Labu, Deli Serdang. Researchers also take a literature study approach and obtain data from sources in the form of books, journals, internet and government publications. And processed as well as possible so that this research is useful for the readers